Chromosome-level genome and multi-omics analyses provide insights into the geo-herbalism properties of Alpinia oxyphylla - Pan, Kun; Dai, Shuiping; Tian, Jianping; Zhang, Junqing; Liu, Jiaqi; Li, Ming; Li, Shanshan; Zhang, Shengkui; Gao, Bingmiao (Frontiers in Plant Science, 2023)
Alpinia oxyphylla Miquel (A. oxyphylla), one of the “Four Famous South Medicines” in China, is an essential understory cash crop that planted widely in Hainan, Guangdong, Guangxi and Fujian provinces. Particularly, A. oxyphylla from Hainan province is highly valued as as the best national product for geo-herbalism and is an important indicator of traditional Chinese medicine efficacy. However, the molecular mechanism underlying the formation of its quality remains unspecified. To this end, we employed a multi-omics approach to investigate the authentic quality formation of A. oxyphylla. In this study, we present a high-quality chromosome level genome assembly of A. oxyphylla, with contig N50 of 76.96 Mb and a size of approximately 2.08Gb. A total of 38, 178 genes were annotated, and the long terminal repeats have a high frequency of 61.70%. Phylogenetic analysis demonstrated a a recent whole-genome duplication event (WGD), which was before A. oxyphylla's divergence from W. villosa (~14 Mya) and shared by other species from the Zingiberaceae family (Ks, ~0.3; 4DTv, ~0.125). Further, 17 regions from four provinces were comprehensively assessed for their metabolite content, the quality of these four regions varied significantly. Finally, Genomic, metabolic, and transcriptomic analyses undertaken on these regions revealed that the content of nootkatone in Hainan was significantly different from that in other provinces. Overall, our findings provide novel insights into germplasm conservation, geo-herbalism evaluation and functional genomic research for the medicinal plant A. oxyphylla.